1989
DOI: 10.1007/bf00930963
|View full text |Cite
|
Sign up to set email alerts
|

Neural and glandular localisation of substance P inEchinostoma caproni (Trematoda-Digenea)

Abstract: Immunocytochemical studies using antibodies against various peptides were performed on Echinostoma caproni. Only the presence of substance P or a related peptide was clearly demonstrated in this digenetic trematode. In the central nervous system, substance P-immunoreactive neurons were few and constituted two populations according to their size. Labelled axons were observed in the ventral and dorsal nerve cords. Scarce, small neurons and fibres were detected in the peripheral nervous system. The comparative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The present investigation has demonstrated, for the first time, the presence and distribution of immunoreactivity to prolactin in the nervous system in Taenia hydatigena and Taenia solium. The demonstration of a large number of the serotoninergic, cholinergic and peptidergic components of the nervous system in platyhelminths have increased substantially in the last ten years (Gustafsson et al , 1985(Gustafsson et al , , 1993(Gustafsson et al , & 1995Basch & Gupta 1988;Gupta & Basch, 1989;Richard et al, 1989;Maule et al, 1990aMaule et al, & 1993. However, there are extraordinary few data on prolactin in the flatworms, especially in the nervous system of them.…”
Section: Discussionmentioning
confidence: 99%
“…The present investigation has demonstrated, for the first time, the presence and distribution of immunoreactivity to prolactin in the nervous system in Taenia hydatigena and Taenia solium. The demonstration of a large number of the serotoninergic, cholinergic and peptidergic components of the nervous system in platyhelminths have increased substantially in the last ten years (Gustafsson et al , 1985(Gustafsson et al , , 1993(Gustafsson et al , & 1995Basch & Gupta 1988;Gupta & Basch, 1989;Richard et al, 1989;Maule et al, 1990aMaule et al, & 1993. However, there are extraordinary few data on prolactin in the flatworms, especially in the nervous system of them.…”
Section: Discussionmentioning
confidence: 99%
“…The immunocytochemical demonstration of vertebrate like peptides (VIP) have been confined to E. liei Whitfield, 1987and Riddell, et al, 1991). Richard et al (1989) detected substance P-like immunoreactivity in the central and peripheral nervous structures and in the glandular cells of the prostate. Riddell, et al(1991),demonstrated the presence of FMRF amide-like immunoreactive cells in the central nervous system and reproductive system of E. liei.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, strong NADPH‐d staining was observed in the prostate gland. Richards et al (1989) reported positive immunostaining for substance P in the prostate gland of Echinostoma caproni . According to Vincent (1995), many neuropeptides, including substance P, are coexpressed together with nNOS in vertebrates.…”
Section: Discussionmentioning
confidence: 99%